2016
DOI: 10.1007/s40292-016-0154-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Dose Atorvastatin Therapy on Baroreflex Sensitivity in Hypertensives

Abstract: An inverse correlation between blood pressure and BRS is present in hypertensives. BRS and BRSf is higher in low dose statin-treated patients with essential hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In this present study, in Table 1, we showed baroreflex sensitivity has been decreased in hypertensive subjects, which was consistent with the established literature. [1619] Blunt peripheral pressure sensors passivation and central cardiovascular regulatory dysfunction could be responsible for the attenuated baroreflex sensitivity. Stiffening and thickening of the aortic wall and of the carotid sinus wall is likely to reduce the baroreceptor afferent impulses, leading to decreasing the sensitivity of aortic and carotid baroreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…In this present study, in Table 1, we showed baroreflex sensitivity has been decreased in hypertensive subjects, which was consistent with the established literature. [1619] Blunt peripheral pressure sensors passivation and central cardiovascular regulatory dysfunction could be responsible for the attenuated baroreflex sensitivity. Stiffening and thickening of the aortic wall and of the carotid sinus wall is likely to reduce the baroreceptor afferent impulses, leading to decreasing the sensitivity of aortic and carotid baroreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…18) In nonobese patients with T2DM and dyslipidemia, low doses of atorvastatin improved BRS; 19) other studies also showed that statin increased BRS. 19,20) As a large percentage of patients with T2DM develop dyslipidemia, proper control of both blood glucose levels and lipid metabolism variables is important to prevent a reduction in BRS. Obesity, insulin resistance, hyperinsulinemia, and hypoadiponectinemia: BRS was reported to be decreased markedly in an obese group compared to a control group, indicating that obesity was a factor in sympathovagal imbalance (increased sympathetic nerve activity and decreased parasympathetic nerve activity).…”
Section: Clinical Features Of Reduced Baroreflex Sensitivitymentioning
confidence: 99%
“…Hypercholesterolemia is a well-known risk factor for the development of atherosclerosis and atherosclerotic changes of the carotid arteries are associated with decreased BRS (Kwiterovich 2002;Nasr et al 2005). Improvement of BRS has also been observed in the statin-treated subjects (Patterson et al 2002;Celovska et al 2016). Additionally, despite role of repeated sympathetic activation in change of BRS and following chronic sympathetic overactivation was supposed (Cortelli et al 2012), this role still remains controversial.…”
Section: Discussionmentioning
confidence: 99%